Understanding post-conflict mental health needs and co-producing a community-based mental health intervention for older adults in Colombia: a research protocol - Clarissa Giebel; Maria Isabel Zuluaga; Gabriel Saldarriaga; Ross White; Siobhan Reilly; Erica Montoya; Dawn Allen; Ginger Liu; Yeferson Castaño-Pineda; Mark Gabbay (BMC, 2022)
Abstract Background Older adults in Colombia have seen a number of stressful life events - including the Colombian armed conflict, forced misplacement and recently COVID-19. These events likely have had and are having a substantial impact on people's mental health and well-being, whilst mental health care provision in Colombia is not sufficient and often access is limited and unaffordable. Therefore, the aim of this study is to understand the impact of stressful life events on the mental health of older adults living in Colombia, and co-produce, pilot, and evaluate a community-based mental health intervention in Turbo. Methods This 3-year international mixed-methods study comprises of three phases: Phase I will explore the impact of stressful life events on the mental health of older adults living in Colombia, and their mental health needs, via quantitative needs assessments and qualitative interviews and focus groups; Phase II will involve synthesising the findings from Phase I as well as conducting a systematic review and qualitative interviews with experts into implementing mental health interventions in LMICs to co-produce a community-based mental health intervention with older adults and local community group leaders and care providers; Phase III will involve the piloting and evaluation of the mental health intervention via quantitative and qualitative assessments. Co-production and public involvement underpin each element of this project. Discussion Appropriate mental health care is as important as physical health care, but this study also looks at how we might integrate these findings into community-level public health initiatives for application both within Colombia and more widely in both LMICs and more developed countries. This study protocol will act as a guide for the development and adaptation of psychosocial mental health interventions in different cultures and contexts.